2021
DOI: 10.3892/ol.2021.12732
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA PCAT6 facilitates cell proliferation and invasion via regulating the miR‑326/hnRNPA2B1 axis in liver cancer

Abstract: Liver cancer is one of the most common malignant human tumors with the highest morbidity and mortality rates of all cancer types in China. Evidence suggests that long non-coding RNA prostate cancer-associated transcript 6 (PCAT6) plays an essential role in tumor progression. However, the roles and mechanism of PCAT6 in liver cancer remain unclear. The present study showed that the expression of PCAT6 and heterogeneous nuclear ribonucleoprotein A2B1 (hnRNPA2B1) was upregulated in liver cancer tissues compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Prostate cancer-associated transcript 6 (PCAT6) is a lncRNA that sponges miR-326, an inhibitor of hnRNPA2B1 expression. PCAT6 is overexpressed in hepatocellular carcinoma and, consequently, the miR-326 level is reduced and that of hnRNPA2B1 enhanced [106], but the exact AS events effected have not yet been determined.…”
Section: Binding Of Ncrnasmentioning
confidence: 99%
“…Prostate cancer-associated transcript 6 (PCAT6) is a lncRNA that sponges miR-326, an inhibitor of hnRNPA2B1 expression. PCAT6 is overexpressed in hepatocellular carcinoma and, consequently, the miR-326 level is reduced and that of hnRNPA2B1 enhanced [106], but the exact AS events effected have not yet been determined.…”
Section: Binding Of Ncrnasmentioning
confidence: 99%
“…The expression of PCAT6 is found to be aberrantly elevated in various human tumor tissues and cell lines compared with matched normal ones, including bladder cancer (BC) [ 21 , 24 , 25 ], breast cancer (BrCa) [ 26 , 27 ], cervical cancer (CC) [ 28 , 29 ], colorectal cancer (CRC) [ 30 , 31 ], gastrointestinal stromal tumor (GIST) [ 32 ], gastric cancer (GC) [ 33 , 34 ], glioblastoma (GBM) [ 35 ], hepatocellular carcinoma (HCC) [ 36 , 37 , 38 ], lung cancer (LC) [ 20 , 39 , 40 , 41 , 42 , 43 ], osteosarcoma (Osa) [ 44 , 45 , 46 ], ovarian cancer (OvCa) [ 47 , 48 ], cholangiocarcinoma (CCA) [ 49 ], pituitary adenoma (PA) [ 50 ], pancreatic ductal adenocarcinoma (PDAC) [ 51 ], and prostate cancer (PCa) [ 52 , 53 ]. In subsequent experiments on the biological functions of tumor cells, it has been revealed that a high level of PCAT6 has strong cancer-promoting effects, mainly including the promotion of cell proliferation, enhancement of migration, invasion and EMT process, as well as the inhibition of cell apoptosis.…”
Section: Expression and Subcellular Localization Of Pcat6mentioning
confidence: 99%
“…In subsequent experiments on the biological functions of tumor cells, it has been revealed that a high level of PCAT6 has strong cancer-promoting effects, mainly including the promotion of cell proliferation, enhancement of migration, invasion and EMT process, as well as the inhibition of cell apoptosis. Meanwhile, PCAT6 has been shown to promote tumor growth and metastasis in xenograft mouse models ( Table 1 ) [ 26 , 29 , 30 , 38 , 39 , 40 , 43 , 44 , 46 , 50 , 52 , 53 , 54 ]. However, Amelia et al reported that the expression level of PCAT6 was opposite in lung tumor tissues and lung cancer cell lines compared with the normal control group [ 55 ].…”
Section: Expression and Subcellular Localization Of Pcat6mentioning
confidence: 99%
See 2 more Smart Citations